2021
DOI: 10.1007/s40123-021-00444-0
|View full text |Cite
|
Sign up to set email alerts
|

Eye Care During the COVID-19 Pandemic: A Report on Patients’ Perceptions and Experiences, an Asian Perspective

Abstract: Introduction To elucidate the perceptions on eye care of patients affected by the disruption of outpatient and surgical ophthalmological services during the COVID-19 pandemic. Methods A cross-sectional questionnaire-based survey was conducted during the reopening of outpatient services at two tertiary eye care centres in Singapore and North India. Consecutive patients were recruited from general and specialist eye clinics in June 2020. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
(39 reference statements)
0
10
0
Order By: Relevance
“…As reported in most COVID-19 studies, the COVID-19 pandemic increased digital and online learning time[ 20 ] and reduced outdoor activities and follow-up. [ 3 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As reported in most COVID-19 studies, the COVID-19 pandemic increased digital and online learning time[ 20 ] and reduced outdoor activities and follow-up. [ 3 ]…”
Section: Discussionmentioning
confidence: 99%
“…In view of this, when it was not possible to effectively increase outdoor activities, health education for parents in the post-pandemic era should strengthen knowledge about near-work activities in daily life to avoid myopia progression. Similar to the study of Low et al ,[ 3 ] patients’ appointments and procedures were put on hold during the lockdown until further notice. In our study, the follow-up intervals were significantly prolonged from 3 to 4 months, and parents reported concerns about contracting COVID-19 in the clinic and felt that COVID-19 had negatively impacted their eye disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 9 10 11 ] Red eye cases, perhaps due to chemical reaction of sanitizers became the most concerned problem during peak COVID. [ 12 13 14 ] Cataract surgeries done during peak covid period, were only for lens induced glaucoma and hypermature cataract and comprised only 12% as compared to pre COVID period. Only 120 minor eye surgeries were done during COVID time which included 85 cases of foreign body removal, 30 cases were incision and curetted for chalazion, 2 epilation cases for trichiasis, and excision of small pterygium in 3 patients.…”
Section: Discussionmentioning
confidence: 99%
“…7 Similarly, a study in India and Singapore also reported the fear of COVID-19 infection as a cause of the decline in patient consults. 8 In response to this crisis, eye care professionals struggled to strike a balance between delivering quality eye care services while mitigating the risk of infection. Various international and local ophthalmologic professional organizations including the American Academy of Ophthalmology, 9,10 Philippine Academy of Ophthalmology, 11 and the Philippine Society of Cataract and Refractive Surgery 12 have issued guidelines on the practice of ophthalmology during the COVID-19 pandemic.…”
mentioning
confidence: 99%